Distributed IT for integration and communication of engineering information for collaborative building design - Fahdah, Ibrahim (2008)
In recent years, the rapid development of new information technologies has significantly impacted on the product development process as strategic means to gain competitive advantage in a global market. In the engineering domain, powerful computer-based tools such as Computer Aided Design systems enable engineers to perform various design tasks and realise product concepts in the early phase of the product development process. However, the increasing complexity of modern products as well as the globalization of product development further necessitate distributed and collaborative design environments. This is where different computer systems and dispersed specialists in similar or different disciplines need to collaboratively be involved in shared design activities. Therefore, the integration and communication of engineering information are two of the most key technical factors in ensuring successful collaboration.